Comparison Of Methods For The Quantification Of Albumin In Serum And Total Protein In Cerebrospinal Fluid - Vanessa Pérez-del-Vallìn; José Alejandro Rodríguez-Pérez; Alejandro Mirabal-Viel; Christian Meijides-Mejías; Jairo Lumpuy-Castillo; William Castillo-González; Alberto Juan Dorta-Contreras (Revista Cubana de Investigaciones Biomédicas, 2019)
Introduction: Albumin is the protein that marks the passage of cerebrospinal fluid proteins into the serum.